Pediatric pain: prevalence, assessment, and management in a teaching hospital - M.B.M. Linhares; F.N.P. Doca; F.E. Martinez; A.P.P. Carlotti; R.G.M. Cassiano; L.I. Pfeifer; C.A. Funayama; L.R.G. Rossi; G.A. Finley (Brazilian Journal of Medical and Biological Research, 2012)
The goal of this study was to examine the prevalence, assessment and management of pediatric pain in a public teaching hospital. The study sample consisted of 121 inpatients (70 infants, 36 children, and 15 adolescents), their families, 40 physicians, and 43 nurses. All participants were interviewed except infants and children who could not communicate due to their clinical status. The interview included open-ended questions concerning the inpatients’ pain symptoms during the 24 h preceding data collection, as well as pain assessment and pharmacological/non-pharmacological management of pain. The data were obtained from 100% of the eligible inpatients. Thirty-four children/adolescents (28%) answered the questionnaire and for the other 72% (unable to communicate), the family/health professional caregivers reported pain. Among these 34 persons, 20 children/adolescents reported pain, 68% of whom reported that they received pharmacological intervention for pain relief. Eighty-two family caregivers were available on the day of data collection. Of these, 40 family caregivers (49%) had observed their child’s pain response. In addition, 74% reported that the inpatients received pharmacological management. Physicians reported that only 38% of the inpatients exhibited pain signs, which were predominantly acute pain detected during clinical procedures. They reported that 66% of patients received pharmacological intervention. The nurses reported pain signs in 50% of the inpatients, which were detected during clinical procedures. The nurses reported that pain was managed in 78% of inpatients by using pharmacological and/or non-pharmacological interventions. The findings provide evidence of the high prevalence of pain in pediatric inpatients and the under-recognition of pain by health professionals.